I can not solve the system.Can any one help me with that? Thanks.

```
ClearAll("Global`*");
f1(S_, e_, I1_, I2_, R_) :=
b*(S + R) - d*S - g*S*(S + e + I1 + I2 + R)/K - bcd*S*(I1 + I2);
f2(S_, e_, I1_, I2_, R_) := -d*e - g*e*(S + e + I1 + I2 + R)/K +
bcd*S*(I1 + I2) - scd1*e;
f3(S_, e_, I1_, I2_, R_) := -d*I1 -
g*I1*(S + e + I1 + I2 + R)/K + (1 - f)*scd1*e - scd2*I1;
f4(S_, e_, I1_, I2_, R_) := -d*I2 - g*I2*(S + e + I1 + I2 + R)/K +
f*scd1*e - acd*I2;
f5(S_, e_, I1_, I2_, R_) := -d*R - g*R*(S + e + I1 + I2 + R)/K +
scd2*I1;
Expand({f1(S, e, I1, I2, R) == 0, f2(S, e, I1, I2, R) == 0,
f3(S, e, I1, I2, R) == 0, f4(S, e, I1, I2, R) == 0,
f5(S, e, I1, I2, R) == 0})
{b R + b S - d S - bcd I1 S - bcd I2 S - (e g S)/K - (g I1 S)/K - (
g I2 S)/K - (g R S)/K - (g S^2)/K ==
0, -d e - (e^2 g)/K - (e g I1)/K - (e g I2)/K - (e g R)/K +
bcd I1 S + bcd I2 S - (e g S)/K - e scd1 ==
0, -d I1 - (e g I1)/K - (g I1^2)/K - (g I1 I2)/K - (g I1 R)/K - (
g I1 S)/K + e scd1 - e f scd1 - I1 scd2 ==
0, -acd I2 - d I2 - (e g I2)/K - (g I1 I2)/K - (g I2^2)/K - (
g I2 R)/K - (g I2 S)/K + e f scd1 ==
0, -d R - (e g R)/K - (g I1 R)/K - (g I2 R)/K - (g R^2)/K - (g R S)/
K + I1 scd2 == 0}
NSolve(%, {S, e, I1, I2, R}, Reals)`
```